A star-shaped polymer used as an additive for optical cable grease and its application
By using star polymer DVB-(E/EP-EP-EP/St-St-R)n as an additive in optical cable paste, the existing gelling agent has simple structure and limited functions have been solved, and the overall performance of optical cable paste is balanced and balanced, especially when synergistically with white carbon black, the thixotropy of the paste is significantly improved.
Patent Information
- Application Number
- CN202411890050.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-04
AI Technical Summary
The existing optical cable paste gelling agent polymer has simple structure and limited functions, making it difficult to balance and balance the comprehensive performance of the paste.
A star polymer DVB-(E/EP-EP-EP/St-St-R)n is used as an optical cable paste additive. Its structure includes a Bd/Ip random copolymerization segment at the near nucleus end and an Ip-Ip/St-St transition copolymerization segment at the far nucleus end, increasing the polar segment and increasing the arm count and polarity.
Through synergistic action, the compatibility, solubility and thixotropy of optical cable paste are improved, and the comprehensive performance of the paste is improved, especially when synergistically with white carbon black, the hydrogen bonding effect is enhanced, and the thixotropy of the paste is further improved.
Smart Images

Figure BDA0005200431440000091
Abstract
Description
Technical Field
[0001] The invention relates to the field of anionic active polymers, in particular to a star-shaped polymer used as an additive for optical cable ointment and application thereof. Background Art
[0002] Optical cable grease is a filler in optical cables. It mainly plays the role of fixing the position of optical fibers, providing mechanical buffering, blocking water, and absorbing hydrogen. It plays an important role in improving the comprehensive performance of optical cables in various complex installation environments. The gelling agent in the optical cable grease is the main contributor to the viscosity of the grease and has a great influence on the comprehensive performance of the grease. Among them, hydrogenated styrene-isoprene diblock copolymer SEP is a commonly used gelling agent for optical cable grease. Foreign companies such as Kraton (brand 1701) and Kuraray (brand 1020), and domestic companies such as Sinopec Baling Branch (brand 4010) and Zhejiang Zhongli (brand 7401) all produce such SEP products.
[0003] As a gelling agent for optical cable grease, SEP has relatively good comprehensive performance, but its structure is relatively simple and its functions are relatively few, making it difficult to balance and take into account the comprehensive performance of the grease. CN112708085B reports a star-shaped SEP with an arm structure of "core-styrene-hydrogenated isoprene", which is formed by direct coupling of SEP at the styrene end; the number of arms is 3-5.5, which is limited by the steric hindrance of the coupled end styrene, the number of arms is relatively small, the number of end groups is small, and the space left for end group modification is relatively small. Summary of the invention
[0004] Considering the problems existing in the existing optical cable grease gelling agent polymer, the present invention proposes a star-shaped polymer used as an optical cable grease additive, and the technical scheme is as follows:
[0005] A star-shaped polymer used as an additive for optical cable grease, the polymer structure is "DVB-(E / EP-EP-EP / St-St-R) n " structure, the star polymer number average molecular weight is 20,000-200,000, the polydispersity index is 1.1-1.5, and the structural formula is "DVB-(Bd / Ip-Ip-Ip / St-St-R) n " is hydrogenated into a copolymer; wherein DVB is the core of the polymer, and E / EP-EP-EP / St-St-R is the arm of the polymer; wherein "E / EP" is a segment formed by random copolymerization of butadiene (Bd) and isoprene (Ip) and then hydrogenation; "EP-EP / St-St" is a segment formed by copolymerization of isoprene (Ip) segments through random copolymerization of isoprene (Ip) segments to styrene (St) segments and then hydrogenation; R is the same or different and is selected from hydrogen or a polar segment; the number of arms n is 6-20, and the molecular weight of a single arm is 0.1-3.3 thousand.
[0006] Preferably, R is the same or different and is selected from hydrogen or a polar segment, and the number of arms of R selected from hydrogen or a polar segment is not zero.
[0007] Before hydrogenation of the "E / EP" segment (ie, the Bd / Ip segment), the total polymerization degree of Bd and Ip is 2-30, and the polymerization degrees of Bd and Ip are both greater than 0.
[0008] Before hydrogenation of the "EP-EP / St-St" chain segment (i.e., Ip-Ip / St-St chain segment), the proportion of block St to total St (i.e., block ratio of St) is 30-90%, the polymerization degrees of the three blocks of Ip, Ip / St, and St are all greater than 0, and the polymerization degrees of Ip and St in the Ip / St block are both greater than 0.
[0009] The polar segments are segments containing terminal hydroxyl groups or segments containing unsubstituted or substituted acrylic acid esters, and the proportion of the number of polar segments to the number of all R groups is 0.1%-90%.
[0010] The segment containing terminal hydroxyl groups is a segment containing n-propanol groups;
[0011] The chain segment containing unsubstituted or substituted acrylate is acrylic acid or methacrylic acid and C1-C 12 The ester formed by the alkyl alcohol has a chain segment formed by homopolymerization or copolymerization, and the degree of polymerization is 1-100, preferably 1-20.
[0012] Further, R is the same or different and is selected from hydrogen or a segment containing a terminal hydroxyl group, and the number of arms of R selected from hydrogen or a segment containing a terminal hydroxyl group is greater than 0;
[0013] Or, R is the same or different and is selected from hydrogen or a segment containing unsubstituted or substituted acrylate, and the arm number of R selected from hydrogen or a segment containing unsubstituted or substituted acrylate is greater than 0.
[0014] The unsubstituted or substituted acrylic acid ester segment and the styrene (St) segment are connected via a capping unit, and the capping unit is a 1,1-diphenylethylene (DPE) unit.
[0015] The hydrogenation degree of the star polymer is above 90%, and the coupling efficiency is above 85%.
[0016] The polymer is used as an additive for optical cable grease.
[0017] The polymer is used together with hydrogenated styrene-isoprene diblock copolymer (SEP) as a gelling agent for optical cable grease and white carbon black as a filler.
[0018] Further, the polymer, hydrogenated styrene-isoprene diblock copolymer (SEP) as a gelling agent for optical cable grease and filler white carbon black are added to industrial white oil, heated and stirred to obtain optical cable grease, wherein the mass fraction of industrial white oil in the optical cable grease is 50-99.9%.
[0019] When used, the mass of the polymer is 1-50% of the mass of the SEP, and the mass of the white carbon black is 0.1-50% of the mass of the SEP.
[0020] The star-shaped polymer in which some arms R are H and some arms R are n-propanol groups is prepared by the arm-first-core-later route, and the St-St / Ip-Ip transition copolymer segment and the Bd / Ip random copolymer segment are polymerized in sequence to prepare the arm in which the terminal group R is H and the arm containing the terminal hydroxyl group, and then the two arm polymer active species are mixed evenly in a certain proportion, coupled, and a hydrogenation catalyst is added for hydrogenation, and then the hydrogenation catalyst is removed, and the hydroxyl protecting group is removed by acid washing, and the star-shaped polymer is obtained after coagulation, filtration, drying and grinding.
[0021] The St-St / Ip-Ip transition copolymer segment is prepared by a batch addition method. St is first polymerized, and after a certain reaction time, Ip is added in batches to obtain a St-St / Ip-Ip transition copolymer segment. The Bd / Ip random block is prepared by a mixed addition method.
[0022] The polymer in which some arms R are H and some arms R are ethyl acrylate segments is prepared by a core-first and arm-later route, a small amount of Bd / Ip mixed monomer is initiated by an initiator to form a Bd / Ip random copolymer unit, and then coupling is performed. After coupling, the Bd / Ip random copolymer segment and the Ip-Ip / St-St transition copolymer segment are polymerized in sequence, the Bd / Ip mixed monomer is added first, and after the polymerization is completed, Ip, Ip / St mixed monomer, and St are added in sequence. After the polymerization is completed, a capping monomer is added, and then tetrahydrofuran is added as a side reaction inhibitor, the polymerization reaction bottle is moved from a warm water bath to an ice water bath, and then unsubstituted or substituted acrylic acid monomer is added to continue polymerization, a terminator is added to terminate the polymerization reaction, and the hydrogenation reactor is added for hydrogenation, and then the hydrogenation catalyst is removed.
[0023] Furthermore, the polymer is prepared by anionic polymerization method, and the specific method is as follows.
[0024] (1) Preparation of star polymers in which some arms R are H and some arms R are n-propanol groups:
[0025] Adding solvent, styrene and initiator 1 into a polymerization reaction bottle 1 to start polymerization, adding isoprene in batches to prepare St-St / Ip-Ip transition copolymer segments, and adding butadiene and isoprene to prepare Bd / Ip random copolymer segments; initiator 1 is one of n-butyl lithium, sec-butyl lithium, tert-butyl lithium, naphthalene lithium, naphthalene sodium and naphthalene potassium;
[0026] Add solvent, styrene and initiator 2 to polymerization reaction bottle 2 to start polymerization, add isoprene in batches to prepare St-St / Ip-Ip transition copolymer segments, and add butadiene and isoprene to prepare Bd / Ip random copolymer segments; initiator 2 is a propyl lithium initiator containing a siloxy group;
[0027] The reaction solutions obtained from polymerization reaction bottles 1 and 2 are mixed and added into polymerization reaction bottle 3, so that the number of polymer molecular chains from polymerization reaction bottle 2 accounts for 0.1-90% of the total number of polymer molecular chains, and coupling agents are added in batches to carry out coupling reaction.
[0028] The product in the polymerization reaction bottle 3 is introduced into a hydrogenation kettle for hydrogenation reaction. After hydrogenation, the catalyst is removed, diluted acid is added for washing to remove the hydroxyl protecting group, and the product is condensed, filtered and dried to obtain the product.
[0029] (2) Preparation of polymers in which some arms R are H and some arms R are polymers containing ethyl acrylate segments:
[0030] Butadiene, isoprene and initiator 1 are added to the polymerization reaction bottle to start polymerization, and then a coupling agent is added. After the coupling is completed, a mixed monomer of butadiene and isoprene, isoprene, a mixed monomer of isoprene and styrene, and styrene are added in sequence for polymerization. After the polymerization reaction is completed, a capping monomer and a side reaction inhibitor are added in sequence. The polymerization reaction bottle is moved into an ice water bath, and unsubstituted or substituted acrylate dissolved in a polar solvent is added so that the molar ratio of the unsubstituted or substituted acrylate to the total number of arm active species is 0.1-90%. The capping monomer is 1,1-stilbene, and the side reaction inhibitor is tetrahydrofuran.
[0031] The product in the polymerization reaction bottle is introduced into a hydrogenation reactor, and a hydrogenation catalyst is added to carry out a hydrogenation reaction. After hydrogenation, the catalyst is removed, and the product is obtained by condensation, filtration and drying.
[0032] Furthermore, (1) a star polymer in which some arms R are H and some arms R are n-propanol groups is prepared by the arm-first and core-later route, and the specific preparation steps are as follows:
[0033] ① Add styrene and initiator 1 to the polymerization reaction bottle 1 containing the non-polar solvent, put the polymerization reaction bottle 1 into a warm water bath to start polymerization, add isoprene in batches at 20min, 40min and 60min of polymerization, and when the total polymerization time is 1.5h, add butadiene and isoprene again, continue the reaction for 0.5h, and the polymerization reaction is completed.
[0034] ② Add styrene and initiator 2 to the polymerization reaction bottle 2 filled with non-polar solvent, put the polymerization reaction bottle 2 into a warm water bath to start polymerization, add isoprene in batches at 20min, 40min, and 60min of polymerization, and when the total polymerization time is 1.5h, add butadiene and isoprene again, continue the reaction for 0.5h, and the polymerization reaction is completed.
[0035] ③ Mix the reaction liquid in polymerization reaction bottle 1 and the reaction liquid in polymerization reaction bottle 2 and add them into polymerization reaction bottle 3, so that the number of polymer molecular chains from polymerization reaction bottle 2 accounts for 0.1-90% of the total number of polymer molecular chains, add coupling agent for coupling, add coupling agent again after 0.5h, and add terminator after 1.5h to terminate the polymerization reaction.
[0036] ④ The product in the polymerization reaction bottle 3 is introduced into the hydrogenation kettle, and then a hydrogenation catalyst is added to carry out a hydrogenation reaction. After hydrogenation, the hydrogenation catalyst is removed, and then washed with dilute acid to convert the hydroxyl protecting group tert-butyldimethylsilyloxy into hydroxyl group, washed to neutrality, and a poor solvent is added to condense, filter, and dry to obtain the product.
[0037] (2) The polymers in which some arms R are H and some arms R are ethyl acrylate segments are prepared by the core-first and arm-later route:
[0038] ① Add butadiene, isoprene and initiator 1 to a polymerization reaction bottle containing a non-polar solvent. After 20 minutes of polymerization, add a coupling agent for coupling, then add butadiene and isoprene. After 20 minutes of polymerization, add isoprene. After 20 minutes, add a mixed monomer consisting of isoprene and styrene. After another 20 minutes, add styrene. After 1 hour, add the capping monomer 1,1-diphenylethylene, react for 0.5 hours, add tetrahydrofuran, a side reaction inhibitor, remove the polymerization reaction bottle from the warm water bath and put it in an ice water bath, add unsubstituted or substituted acrylate dissolved in a polar solvent, so that the molar ratio of unsubstituted or substituted acrylate to the total number of arm active species is 0.1-90%, and after 1 hour of polymerization, add a terminator to terminate the polymerization reaction.
[0039] ② The rubber solution in the polymerization reaction bottle is introduced into the hydrogenation reactor, and a hydrogenation catalyst is added to carry out a hydrogenation reaction. After hydrogenation, the catalyst is removed, and the product is obtained by condensation, filtration and drying.
[0040] The polymerization temperature is 40-60°C;
[0041] The non-polar solvent used in the preparation process is one or more of cyclohexane, n-hexane, n-heptane and n-octane, preferably cyclohexane.
[0042] Initiator 1 is one of n-butyl lithium, sec-butyl lithium, tert-butyl lithium, naphthalene lithium, naphthalene sodium, and naphthalene potassium, preferably n-butyl lithium.
[0043] Initiator 2 is a propyl lithium initiator containing a siloxy group, which is prepared by reacting siloxy chloropropane with lithium metal. The siloxy group is used as a protective group, and can be acid-washed to generate terminal hydroxyl groups after the reaction of preparing the polymer is completed. The present invention selects tert-butyl dimethyl siloxy propyl lithium initiator, which is prepared by reacting tert-butyl dimethyl siloxy chloropropane with lithium metal. The preparation method is shown in the reference: Chen Jiming, Master's thesis of Shandong University, 2010, which is cited as a known technology in the art.
[0044] The terminator of the polymerization reaction is isopropanol.
[0045] The hydrogenation catalyst is a Ziegler-Natta catalyst, which is prepared by compounding nickel cyclohexaneate and triisobutyl aluminum. The hydrogenation reaction method can be referred to in the following literature: Synthetic Rubber Industry, 2003, 26(2): 122-125; Polyurethane Industry, 2022, 37(1): 24-27; Yu Yueman, Master's Thesis of Shandong University of Technology, 2022; CN104628901B. The amount of catalyst added is 0.01-10 mg nickel / 1 g dry rubber, and the molar ratio of aluminum to nickel is 0.01-10; the hydrogenation reaction temperature is 10-100°C, and the hydrogen pressure is 0.01-10 MPa.
[0046] After the hydrogenation reaction is completed, the hydrogenation catalyst needs to be removed, and any catalyst removal method commonly used in the art can be used, references: Elastomer, 2012, 22 (5): 34-37; CN101333264B; CN102977230B; CN113912796B; CN114316094B. In the product of the hydrogenation catalyst removal, the nickel content is preferably less than 10 ppm, and the aluminum content is preferably less than 30 ppm.
[0047] After removing the hydrogenation catalyst, the hydroxyl protecting group tert-butyldimethylsilyloxy at the outer end of the arm is converted into a hydroxyl group by acid washing. After acid washing, one or more water washings can be performed to remove the remaining acid in the product, so that the pH of the product glue solution is preferably controlled between 6.5 and 7.5. The washing method is shown in the reference: Chen Jiming, Master's thesis of Shandong University, 2010.
[0048] The poor solvent is methanol, ethanol, propanol, water, etc. The poor solvent is used for condensation to precipitate the product, which is then filtered and dried to obtain the product.
[0049] Before polymerizing the (meth)acrylate segments, a certain amount of refined polar solvent needs to be added as a co-solvent. The polar solvent may be selected from weak polar solvent toluene, strong polar solvent tetrahydrofuran (THF), etc. In the present invention, toluene is selected.
[0050] The polymerization reaction method of (meth)acrylate monomers can be found in the following references: RSC Advances, 2017, 7(16): 9933-9940; Elastomers, 2020, 30(2): 46-50; CN101429256B; CN112480292A.
[0051] The unsubstituted or substituted acrylate is (meth)acrylate, which can be selected from methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, and lauryl (meth)acrylate, and can be homopolymerized with one monomer or copolymerized with a plurality of monomers. The present invention preferably uses methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, and butyl (meth)acrylate, and more preferably uses methyl (meth)acrylate and ethyl (meth)acrylate.
[0052] The advantages and beneficial effects of the present invention are as follows:
[0053] The present invention creatively provides a star polymer DVB-(E / EP-EP-EP / St-St-R) n The polymer has a small steric hindrance near the core end, which can increase the number of arms; the polar chain segment is connected to the far core end to increase the polarity of the polymer. The polymer of the present invention is used as an additive for optical cable ointment through the synergistic effect of each chain segment, and is used together with the commonly used optical cable ointment components - gelling agent hydrogenated styrene-isoprene diblock copolymer (SEP) and filler white carbon black to improve the comprehensive performance of the optical cable ointment. The details are as follows:
[0054] (1) Using the Ip-Ip / St-St (EP-EP / St-St after hydrogenation) transition copolymer chain segment as the main structure of the polymer arm, the compatibility of the polymer with SEP and the solubility of the polymer in the white oil matrix are improved; the Ip and St homopolymer segments are retained to maintain the dropping point, cone penetration, and steel mesh oil separation performance of the ointment;
[0055] (2) Arrange Bd / Ip (E / EP after hydrogenation) random copolymer segments near the core end, and arrange Ip-Ip / St-St (EP-EP / St-St after hydrogenation) transition copolymer segments from inside to outside to minimize the steric hindrance near the core end and increase the number of arms of the product;
[0056] (3) The polar groups are modified at the end of the arm, which can fully contact with the filler and other components in the ointment, play the role of interacting with the filler to build hydrogen bonds and improve the thixotropy of the ointment, while avoiding excessive polar groups that lead to reduced solubility of the polymer and compatibility of components, thereby avoiding macroscopic phase separation of the ointment. DETAILED DESCRIPTION
[0057] The present invention will be further described below in conjunction with specific embodiments.
[0058] The solvent, polymerized monomer, and gas (nitrogen or argon) used in the preparation process of the present invention are all refined to remove water and oxygen impurities therein, and any refining method commonly used in the art can be selected. The present invention selects to use molecular sieves and copper catalysts to remove impurities in the solvent, calcium hydride water absorption, normal pressure or reduced pressure distillation to remove impurities in the polymerized monomer (except butadiene), n-butyl lithium pre-impurity removal method to remove impurities in butadiene, and a deoxidation tube to remove impurities in the gas. The water and oxygen impurity content of the refined material is preferably reduced to below 10ppm.
[0059] Example 1: Preparation of a star polymer in which some arms R are H and some arms R are n-propanol groups.
[0060] The glass containers used in the preparation process are baked and purged with inert gas to remove water and oxygen impurities. During the operation, pay attention to keep the inside of the container and the materials clean to avoid bringing water and oxygen impurities into the reaction system.
[0061] Polymerization: Prepare and titrate tert-butyldimethylsiloxypropyl lithium initiator according to the method described in the literature (Chen Jiming, Master's thesis of Shandong University, 2010). Use a 500mL three-necked flask equipped with water bath heating, magnetic stirring, inert gas purge pipeline, condensation reflux tube and closed feeding funnel. Add the solvent cyclohexane 120mL, tert-butyldimethylsiloxy chloropropane 50g and metal lithium 13g in proportion, start dripping tert-butyldimethylsiloxy chloropropane cyclohexane solution at a reaction temperature of 40°C, drip it for 1h, heat it to 60°C and continue the reaction for 5h, let it stand overnight, and complete the preparation of tert-butyldimethylsiloxypropyl lithium initiator. The concentration of the initiator solution is 0.77mol / L after titration.
[0062] Three 1L single-mouth round-bottom flasks were used as polymerization reaction bottles, heated in a 50°C water bath, equipped with magnetic stirring, and the bottle mouths were sealed with reverse-mouth rubber stoppers. Polymerization reaction bottles 1 and 2 were each filled with 450g of cyclohexane solvent. Polymerization reaction bottle 1 was initiated with 1.6mol / L n-butyl lithium hexane solution, and polymerization reaction bottle 2 was initiated with a homemade tert-butyl dimethylsiloxypropyl lithium solution, and the arm polymerization was performed separately. Polymerization reaction bottle 3 was left empty for coupling.
[0063] In a polymerization reaction bottle 1 containing 450g of cyclohexane solvent, 15g of styrene was added, and 1.9mL of 1.6mol / L n-butyl lithium hexane solution was added for initiation. 10g of isoprene was added at 20min, 40min, and 60min of polymerization. When the total polymerization time was 1.5h, 1g of butadiene and 1g of isoprene were added, and the reaction was continued for 0.5h. The sample was analyzed by gel permeation chromatography (GPC), and the molecular weight was 22,000 and the polydispersity index was 1.12.
[0064] In the polymerization reaction bottle 2 containing 450g of cyclohexane solvent, 15g of styrene was added, and 3.7mL of self-made 0.77mol / L tert-butyldimethylsiloxypropyl lithium solution was added for initiation. 10g of isoprene was added at 20min, 40min, and 60min of polymerization. When the total polymerization time was 1.5h, 1g of butadiene and 1g of isoprene were added, and the reaction was continued for 0.5h. The sample was analyzed by gel permeation chromatography (GPC), and the molecular weight was 24,000 and the polydispersity index was 1.13.
[0065] In polymerization reaction bottle 3, 400g of reaction solution was introduced from polymerization reaction bottle 1 with a double-headed guide needle, and 146g of reaction solution was introduced from polymerization reaction bottle 2, so that the molar ratio of the active chain initiated by n-butyl lithium to the active chain initiated by the protective group initiator was 3 (the total mass of the monomer was divided by the molecular weight measured by GPC to obtain the molar number of the active chain, which was compared with the total mass of the glue to obtain the molar concentration of the active chain, thereby determining the mass of the introduced reaction solution). Maintain the temperature at 50°C and stir for 10 minutes to mix the reaction solution evenly. Add 0.8g of divinylbenzene for coupling, add another 0.8g of divinylbenzene after 0.5h, add 0.16g of isopropanol after 1.5h to terminate the reaction, and continue stirring for 10 minutes to terminate the polymerization reaction. Samples were analyzed by gel permeation chromatography (GPC), and the total molecular weight (number average molecular weight) was 175,000, the polydispersity index was 1.26, the average number of arms was 7.6, and the coupling efficiency was 92.1%.
[0066] Hydrogenation: After the inner wall of the 1L hydrogenation reactor is cleaned, it is purged and replaced with nitrogen for 3 times. The glue liquid in the polymerization reaction bottle 3 is introduced into the hydrogenation reactor with a double-headed guide needle, so that the glue liquid does not contact water and oxygen impurities during the introduction into the hydrogenation reactor. The hydrogenation reactor is heated to 60°C. Prepare nickel cyclohexaneate-triisobutylaluminum catalyst (refer to the method described in the literature: Synthetic Rubber Industry, 2003, 26 (2): 122-125), add materials according to 3 mg nickel / 1 g dry glue and 3.5 aluminum-nickel molar ratio. After the preparation is completed, age in a 60°C water bath for 20 minutes. Then the catalyst is introduced into the hydrogenation reactor with a double-headed guide needle and stirred for 10 minutes. The catalyst does not contact water and oxygen impurities during preparation and introduction into the hydrogenation reactor. Hydrogen is introduced into the hydrogenation reactor, purged and replaced 3 times, and then hydrogen is introduced to a pressure of 2.5 MPa, and the hydrogenation reaction is started. The hydrogen is continuously introduced into the hydrogenation reactor for a reaction time of 4 hours. The hydrogenation reaction was stopped, the hydrogen was released, and the hydrogen was purged and replaced with nitrogen three times to complete the hydrogenation.
[0067] Post-treatment: Remove the hydrogenation catalyst in the glue solution by referring to the method described in the literature (Elastomer, 2012, 22(5): 34-37), then wash with dilute hydrochloric acid to remove the hydroxyl protecting group tert-butyldimethylsilyloxy to convert it into hydroxyl, and then wash with water until neutral (pH controlled between 6.5-7.5). Pour the glue solution into ethanol for coagulation, filter, and dry to obtain the product.
[0068] Product analysis: Sampling and analysis of H NMR spectrum showed that the degree of hydrogenation was 98.3%, and the block ratio of styrene (the ratio of block styrene to total styrene (random + block)) was 73.5%. Sampling was analyzed by gel permeation chromatography (GPC), and the arm molecular weight was 23,000, the total molecular weight was 178,000, the polydispersity index was 1.26, the average number of arms was 7.7, and the coupling efficiency was 91.9%. Sampling was analyzed by inductively coupled plasma emission spectroscopy (ICP), and the nickel content was 8.5ppm and the aluminum content was 27.8ppm.
[0069] Example 2: Preparation of a polymer in which part of the arm R is hydrogen and part of the arm R contains an ethyl acrylate segment.
[0070] Polymerization: Use a 1L single-mouth round-bottom flask as the polymerization reaction bottle, heat it in a 50°C water bath, add magnetic stirring, seal the bottle mouth with a reverse-mouth rubber stopper, and fill it with 450g of cyclohexane solvent. Initiate with 1.6mol / L n-butyl lithium hexane solution.
[0071] Add 1g butadiene and 1g isoprene to a polymerization reaction bottle containing 450g cyclohexane solvent and stir for 10min. Add 2mL 1.6mol / L n-butyl lithium hexane solution to initiate, add 1.4g divinylbenzene after 20min of polymerization, and couple for 30min. Add 1g butadiene and 1g isoprene, and polymerize for 20min. Add 6g isoprene, and after 20min, add a mixed monomer consisting of 24g isoprene and 12g styrene, and after another 20min, add 3g styrene. After 1h, add 0.5g capping monomer 1,1-diphenylethylene and react for 0.5h. Samples were analyzed by gel permeation chromatography (GPC), and the arm molecular weight was 22,000. The molar amount of the arm active species was obtained by dividing the total mass of the monomers constituting the arm by the arm molecular weight.
[0072] Add 6.2g of tetrahydrofuran, remove the polymerization reaction bottle from the water bath, put it into an ice water bath, and keep stirring. When the temperature of the reaction system drops to 6°C, add 0.06g of ethyl acrylate diluted with 1.1g of toluene to make the molar ratio of the arm active species to ethyl acrylate 4. After 1h of polymerization, add 0.16g of isopropanol and continue stirring for 10min to terminate the polymerization reaction.
[0073] The sample was analyzed by gel permeation chromatography (GPC), and the arm molecular weight was 23,000, the total molecular weight was 156,000, the polydispersity index was 1.32, the average number of arms was 6.8, and the coupling efficiency was 94.3%.
[0074] Hydrogenation: After the inner wall of the 1L hydrogenation reactor is cleaned, it is purged and replaced with nitrogen 3 times. The glue in the polymerization reaction bottle is introduced into the hydrogenation reactor with a double-headed guide needle, so that the glue does not contact water and oxygen impurities during the introduction into the hydrogenation reactor. The hydrogenation reactor is heated to 60°C. Prepare nickel cyclohexane acid-triisobutylaluminum catalyst, feed according to nickel 4mg / 1g dry glue and aluminum-nickel molar ratio of 3.5, and age in a 60°C water bath for 20min after preparation. Then the catalyst is introduced into the hydrogenation reactor with a double-headed guide needle and stirred for 10min. The catalyst does not contact water and oxygen impurities during preparation and introduction into the hydrogenation reactor. Hydrogen is introduced into the hydrogenation reactor, purged and replaced 3 times, and then hydrogen is introduced to a pressure of 2.5MPa, and the hydrogenation reaction is started. The hydrogen is continuously introduced into the hydrogenation reactor for a reaction time of 6h. Stop the hydrogenation reaction, release hydrogen, purge and replace with nitrogen 3 times to complete the hydrogenation.
[0075] Post-treatment: Remove the hydrogenation catalyst in the glue solution by referring to the method described in the literature (Elastomer, 2012, 22(5): 34-37). Pour the glue solution into ethanol for coagulation, filter and dry to obtain the product.
[0076] Product analysis: Sampling analysis of H NMR spectrum showed a hydrogenation degree of 97.0% and a styrene block ratio of 70.2%. Sampling analysis by gel permeation chromatography (GPC) showed an arm molecular weight of 23,000, a total molecular weight of 159,000, a polydispersity index of 1.31, an average arm number of 6.9, and a coupling efficiency of 93.8%. Sampling analysis by inductively coupled plasma emission spectroscopy (ICP) showed a nickel content of 9.4 ppm and an aluminum content of 29.3 ppm.
[0077] Example 3: Preparation of base ointment.
[0078] The materials are shown in Table 1, ensuring that the ratio of the sum of the mass of the homemade polymer and the commercially available hydrogenated styrene-isoprene diblock copolymer (SEP, brand name: Kraton 1701) to the mass of No. 32 industrial white oil is 1:9, and the mass of white carbon black is 2% of the sum of the mass of the homemade polymer and SEP. The homemade polymer, SEP, and white carbon black are mixed and added to the industrial white oil, heated to 100°C, and stirred for 5 hours to obtain a base oil paste.
[0079] The test method for the application performance of base ointment is as follows.
[0080] (1) Test the dropping point according to the national standard GB / T 4929-1985;
[0081] (2) Test the cone penetration (25°C, 150g, 1 / 10mm) in accordance with the national standard GB / T 269-2023;
[0082] (3) Test the oil separation rate of steel mesh according to the industry standard NB / SH / T 0324-2010, the test temperature is 100℃, and the test time is 30h;
[0083] (4) The thixotropy index is characterized by the "thinning index", which is the ratio of the viscosity measured by a cone-plate viscometer at a rotation speed of 3 rpm (low shear) and 100 rpm (high shear), the test temperature is 25°C, and the test time is 1 min. The thinning index reflects the shear thinning performance of the paste, that is, positive thixotropy. The larger the thinning index, the stronger the thixotropy of the paste and the smaller the pumping resistance, which is beneficial to reducing energy consumption in the optical cable manufacturing process.
[0084] Table 1 Base ointment composition and application performance
[0085]
[0086] It can be seen that the product prepared according to the present invention can improve the dropping point and thixotropy of the base ointment without losing the oil separation performance of the steel mesh; the impact on the cone penetration is small, and the application requirements of cone penetration ≥ 300 mm can still be well met; under the condition of synergistic effect with white carbon black, the product prepared according to the present invention can produce more hydrogen bonds with white carbon black, which helps to further improve the thixotropy of the ointment.
[0087] In summary, the product prepared according to the present invention is used as an additive for optical cable grease, and can improve the comprehensive performance of the optical cable grease by acting alone or in synergy with white carbon black.
[0088] Although the present invention has been described to a certain extent, it is obvious that appropriate changes in various conditions can be made without departing from the spirit and scope of the present invention. It is understood that the present invention is not limited to the embodiments described, but belongs to the scope of the claims, which includes equivalent replacements of each factor described.
Claims
1. A star-shaped polymer used as an additive for optical cable grease, characterized in that: The polymer is "DVB-(E / EP-EP-EP / St-St-R) n " structure, the polymer number average molecular weight is 20,000-200,000, DVB is the core of the polymer, and E / EP-EP-EP / St-St-R are the arms of the polymer; wherein, "E / EP" is a segment formed by random copolymerization of butadiene Bd and isoprene Ip and then hydrogenation; "EP-EP / St-St" is a segment formed by copolymerization of isoprene Ip segment through transition of isoprene Ip / styrene St random copolymerization segment to styrene St segment and then hydrogenation; R is the same or different and is selected from hydrogen or polar segment; the number of arms n is 6-20, and the molecular weight of a single arm is 1,000-33,000.
2. The polymer according to claim 1, characterized in that Before the "E / EP" chain segment is hydrogenated, the total polymerization degree of Bd and Ip is 2-30, and the polymerization degree of Bd and Ip are both greater than 0.
3. The polymer according to claim 1, characterized in that Before hydrogenation of the "EP-EP / St-St" chain segment, the ratio of block St to total St (i.e., the block ratio of St) is 30-90%, the polymerization degrees of the three blocks of Ip, Ip / St, and St are all greater than 0, and the polymerization degrees of Ip and St in the Ip / St block are both greater than 0.
4. The star polymer according to claim 1, characterized in that The polar segments are segments containing terminal hydroxyl groups or segments containing unsubstituted or substituted acrylic acid esters, and the proportion of the number of polar segments to the number of all R groups is 0.1%-90%.
5. The star polymer according to claim 4, characterized in that The segment containing terminal hydroxyl groups is a segment containing n-propanol groups; The chain segments containing unsubstituted or substituted acrylates are acrylic acid or methacrylic acid and C1-C 12 The ester formed by alkyl alcohol is a chain segment formed by homopolymerization or copolymerization, and the degree of polymerization is 1-100.
6. The star polymer according to claim 5, characterized in that The unsubstituted or substituted acrylic ester segment and the styrene (St) segment are connected via a capping unit, and the capping unit is a 1,1-diphenylethylene (DPE) unit.
7. The star polymer according to claim 1, characterized in that The hydrogenation degree of the star polymer is above 90%, and the coupling efficiency is above 85%.
8. An application of the star-shaped polymer according to claim 1, characterized in that: The polymer is used as an additive for optical cable grease.
9. The use of the star polymer according to claim 8, characterized in that: The polymer is used together with hydrogenated styrene-isoprene diblock copolymer (SEP) as a gelling agent for optical cable grease and white carbon black as a filler.
10. The use of the star polymer according to claim 9, characterized in that: When used, the mass of the polymer is 1-50% of the mass of the SEP, and the mass of the white carbon black is 0.1-50% of the mass of the SEP.
Citation Information
Patent Citations
Method for removing residual hydrogenation catalyst after hydrogenation for nonsaturated polymers
CN101333264B
Method for controlling anionic polymerization reaction
CN101429256B
Method for removing hydrogenation catalyst in polymer solution
CN102977230B
Partially hydrogenated terpolymer rubber with star block structure and its preparation method and application
CN104628901B
Method for preparing high-molecular polymer through anionic polymerization of alkyl acrylate polar monomers
CN112480292A